Optimal control of piezoelectric anisotropic plates - Figueiredo, Isabel Narra (2006)
This paper is concerned with the application of optimal control techniques to a static piezoelectric anisotropic thin plate model. To take physical limitations into account, the space of electric potential fields is restricted, i.e., control constraints are imposed. After deriving the first-order necessary conditions for the problem, a primal-dual active set strategy for its solution is presented. In a numerical study we consider a plate composed of two layers of different piezoelectric materials. We investigate the abilities of our approach and the influence of certain parameters.